Modulation of isometric quadriceps strength in soccer players with transcranial direct current stimulation: a crossover study - Vargas, V. Z.; Baptista, A. F.; Pereira, G. O. C.; Pochini, A. C.; Ejnisman, B.; Santos, M. B.; João, S. M. A.; Hazime, F. A. (The Journal of Strength and Conditioning Research, 2018)
The aim of this study was to evaluate the effect of transcranial direct current stimulation (tDCS) on the maximum isometric muscle contraction (MVIC) of the knee extensors in soccer players at the preprofessional level. Twenty female soccer players aged 15-17 years (mean = 16.1; SD = 0.9) with 5.2 ± 2.6 years of training were randomly divided into 2 groups to receive either active or sham tDCS in a single session (2 mA; 0.057 mA·cm-2). The MVIC of the knee extensors was evaluated in both lower limbs by manual dynamometry in 5 sets of contractions divided into 4 blocks: (a) prestimulation, (b) during tDCS, (c) 30 minutes after tDCS, and (d) 60 minutes after tDCS. After an interval of 7 days, the groups were evaluated again, and the type of initial stimulation was inverted between participants. The MVIC of the knee extensors increased significantly during active tDCS (dominant limb (DL) = 0.4; IC = 0.1-0.8 N/Kg), 30 minutes after active tDCS (DL = 0.9; IC 0.4-1.4 N/Kg), and 60 minutes after active tDCS (DL = 1.0; IC 0.3-1.6 N/Kg) but not for sham tDCS. Our conclusion was that tDCS temporarily increases isometric quadriceps strength in adolescent female soccer players, which may be useful for both strength training and rehabilitation.